Long term effect of intravenous immunoglobulins and oral cyclophosphamide in multifocal motor neuropathy. Issue 6 (1st December 1997) - Meucci, Nicoletta; Cappellari, Alberto; Barbieri, Sergio; Scarlato, Guglielmo; Nobile-Orazio, Eduardo
Abstract : Objectives —To report the long term effect of the combined treatment with high dose intravenous immunoglobulins (IVIg) and oral cyclophosphamide (CTX) in patients with multifocal motor neuropathy, and to determine whether the association of oral CTX in these patients may help to delay and, possibly, suspend IVIg infusions. METHODS: Six patients with multifocal motor neuropathy responding to an initial course of IVIg (0.4 g/kg/day for five consecutive days) were followed up for 37 to 61 (mean 47) months. All patients were subsequently treated with periodic IVIg infusions (0.4 g/kg/day for two days at clinical worsening) and oral CTX (1-3 mg/kg/day). Improvement was assessed using the Rankin disability scale, a functional impairment scale for upper and lower limbs, and the MRC rating scale on the 20 most affected muscles. Electrophysiological and antiglycolipid antibody studies were performed before treatment, then yearly during follow up. RESULTS: All patients improved during treatment and, by the end of follow up or before worsening after therapy suspension, the median Rankin (P=0.0335) and upper (P=0.0015) and lower limb (P=0.0301) impairment scores and the mean MRC (P=0.0561) score were improved. By that time the number of nerves with partial motor conduction block was reduced (P=0.0197) and antiglycolipid antibody titres had decreased in all but one patient. All patients required periodic IVIg infusions to maintain improvement but, after three to seven months of oral CTX, the interval between IVIg infusions could be progressively prolonged until, in three patients, both treatments could be stopped for up to two years before clinical worsening. The main complications, both related to oral CTX, were haemorrhagic cystitis in two patients and persistent amenorrhea in one patient. Conclusions— IVIg can induce and maintain improvement in multifocal motor neuropathy but does not eradicate the disease. Oral CTX may help to induce a sustained remission but it is not devoid of side effects and might therefore be reserved for patients with multifocal motor neuropathy who require frequent IVIg infusions to maintain improvement.